Perubahan Pola Bermain Anak Di Era Digital Dan Dampaknya Terhadap Nilai Sosial - Fatimah; Muslim; Ade S Anhar (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
The research is motivated by the increasing use of gadgets in early childhood which affects their play activities and social interactions. This research aims to determine changes in children's play patterns in the digital era; its impact on early childhood social values; as well as what factors affect changes in children's play patterns and social values at Jia State Kindergarten, Sape District. This study uses a descriptive qualitative approach with the research subjects consisting of 32 early childhood children and 6 teachers. Data collection is carried out through observation, interviews, and documentation, while data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study show that there has been a change in children's play patterns from traditional games to digital-based games such as games and videos on gadgets. Schools still direct children to play traditional games and use Educational Game Tools (APE), but the influence of digital media is still seen in children's play activities. The positive impact of changes in play patterns can be seen in the increase in children's ability to recognize technology and visual creativity. However, the negative impact is more dominant, namely decreased social interaction, cooperation, communication, empathy, and compliance with the rules of playing together. Some of the factors that affect the relationship between digital play patterns and children's social values include: parenting patterns; intensity of use of gadgets; the role of teachers in schools; the child's social environment; and digital game types. This study emphasizes the importance of parental supervision and the role of teachers in balancing the use of digital media with children's social play activities